A Reappraisal of the Luroy, Norway, Earthquake of 31 August 1819 - Mäntyniemi, Päivi Birgitta; Sørensen, Mathilde B.; Tatevossian, Tatiana N.; Tatevossian, Ruben E.; Lund, Björn (Seismological Research Letters, 2021)
Archives and libraries were visited to find previously unknown documents testifying to the Luroy, Norway, earthquake of 31 August 1819 in northernmost continental Europe. The focus here is on Sweden, Finland, and Russia, which are important for determining the area of perceptibility east of Norway. The new written sources include 12 notes or entries in original archived documents, six contemporary newspaper reports, and two recollections written down years later. The original documentation uncovered is contributory to establishing the authenticity of the observations in Finland and Sweden. The dates of the original documentation allow tracing of the dissemination of eyewitness accounts in writing from the inner area of perceptibility southward to the larger documentation and population centers. New sources of information include weather reports of the Royal Swedish Academy of Sciences, minutes of its meetings, and correspondence sent to the Senate in Finland. The minutes of meetings of the Academy indicate that ample data were collected in the Swedish province of Vasterbotten. We found no original Russian documentation but uncovered national newspapers that are more reliable than the previously used Parisian newspaper. To increase transparency, we provide the first list of macroseismic data points (MDPs) including the respective documentation that testify to the Luroy earthquake. A macroseismic intensity was assigned to a locality, using the European Macroseismic Scale of 1998, when adequate information was available. Accounting for the uncertainty of intensity assessment, the magnitude was estimated as moment magnitude M = 5.9 +/- 0.2, reconfirming the ranking as the largest onshore or nearshore earthquake in the historical seismicity record of Fennoscandia. In addition to the reappraisal of the 31 August 1819 earthquake, a macroseismic map is provided for the earthquake of 17 February 1819, which was felt in northern Finland and Sweden. Some of its MDPs were previously associated with the Luroy earthquake. ...